Environmental Protection Based on Islamic Law and Epistemology in Indonesia - Sunardi; Trias Hernanda; Naili Azizah; Dian Rosita (Law and Justice, 2023)
Indonesia is the largest Muslim country in Southeast Asia. However, this does not guarantee that the implementation of a diverse Islamic life can run well, environmental damage is an example. As a result of the environmental damage, seasonal disasters always hit Indonesia. Based on Islamic epistemology, environmental damage is proof that environmental protection is not going well. If an understanding of Islam is really carried out properly, then humans will protect nature as if they take care of themselves, so the purpose of this study is to reveal the role of the meaning of Islamic epistemology in providing an understanding of environmental protection. This type of research uses normative legal research, namely legal research conducted based on statutory regulations and library materials. Related to this type of research, the approach used in this paper is a conceptual approach to law and a historical approach. The final result of this research is the role of understanding Islamic epistemology in helping environmental protection is very real and useful if it is understood more deeply and applied properly